Response of Nitrogen and Sulphur Fertilizers on Yield, Yield Components and Protein Content of Oilseed Mustard (Brassica spp) - Mohiuddin, M.; Paul, A. K.; Sutradhar, G. N. C.; Bhuiyan, M. S. I.; Zubair, H. M. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted in the experimental field of Sher-e-Bangla Agricultural University, to observe the effect of different levels of nitrogen and sulphur on growth, yield, yield contributing characters and protein content in seed of mustard (SAU Sharisha-1). The experiment consists of four levels of nitrogen i.e. fertilizer treatments consisted of 4 levels of nitrogen (0, 40, 80 and 120 kg N ha-1 designated as N0, N1, N2 and N3, respectively) and 4 levels of sulphur (0, 8, 16 and 24 kg S ha-1 designated as S0, S1, S2 and S3 respectively).The experiment was laid out in the two factors RCBD with three replications. The plant height, the number of branches plant-1, the number of siliqua plant-1, seed and shoot yield increased with increasing N level up to 80 kg N ha-1. Further increasing in N level i.e. 120 kg N ha-1 had a negative effect on seed yield. On the other hand , with increasing S levels plant height, slilqua plant-1, 1000 seed weight increased significantly up to 16 kg S ha-1. However, the number of branches plant-1 and seed yield and shoot yield increased up to the highest dose of S (24 kg S ha-1). Considering the combined effect of N and S, the treatment combination N2S3 produced the maximum seed yield (1738 kg ha-1). Protein content increased from 19.38% to 21.81% as S rate was increased from 0 to 16 kg ha-1. The highest N level resulted in the highest values for protein (22.31%).